The Invisible Subordination of the Parsi Women: The Crow Eaters - Kiranmai, M. (International Journal of English Literature and Social Sciences (IJELS), 2019)
The paperthrows light on the myriads of Parsi culture and tradition.It explores the hypocrisy and double standards of the male patriarchy of Parsis society in The Crow Eaters.The paper conveys that several forms of the social system are both unjust and oppressive for women.Though the characters are drawn in the novel are perfectly fictitious, there are striking similarities with ordinary and real Parsi people rooted deeply into their age-old culture and tradition.